Fluorescent nanocomposites loaded hydrogels as a theranostic platform for advanced healthcare applications: Recent trends and opportunities - Sood A.; Das S.S.; Dev A.; Bhardwaj D.; Kumar A.; Agrawal G.; Han S.S. (My University, 2025)
With the persistent escalating exigence for new avenues in drug delivery strategies and imaging applications, different novel and efficient nanomaterials have surfaced. The league of these nanomaterials demonstrates many unique properties of which exceptional optical signals are exceedingly investigated. The confinement within the nano range endows exclusive optical attributes that can be explored in the domain of bioimaging and fluorescence-based detections. Despite the innovation in engineering fluorescent nanoparticles (FNPs) with exceptional properties, still, the appetite to develop highly efficient FNPs with multimodal utility can be perceived. Up recently, hydrogels have been projected as an excellent entrant for biomedical applications, due to their biocompatible and biodegradable nature with excellent absorption capacity along with tunable mechanical features. These hydrogels are capable to provide a favourable microenvironment for cellular growth and proliferation. In this critical review article, FNPs conjugated hydrogels (FH) have been critically evaluated for their role in drug delivery and imaging applications. The article will describe the rationale for the origin of fluorescence in FNPs and will also highlight different fabrication methodologies for their synthesis. Further, the utility of these hybrid FH in terms of drug delivery and imaging will be critically discussed and evaluated in detail. Finally, attention will be given to the limitations of these fascinating hybrid hydrogels that limit their clinical translations followed by their prospects that will be decisive for their clinical implications. © 2023 Elsevier Ltd